Potential of Volatile Organic Compounds in the management of insect pests and diseases of chickpea - Makhlouf, Leila; Maafa, Ilyass; Boulamtat, Rachid; El-Fakhouri, Karim; Aasfar, Abderrahim; Kemal, Seid Ahmed; Meftah Kadmiri, Issam; El Bouhssini, Mustapha (2024)
Chickpea (Cicer arietinum) is the second legume crop cultivated in Morocco after the Faba bean, and presents economical and nutritional benefits. However, the crop productivity is low due to biotic factors and drought. Ascochyta blight (Didymella rabiei), Fusarium wilt (Fusarium oxysporum f.sp. Ciceris), and leaf miner (Liriomyza cicerina) are key production constraints in spring-planted chickpeas.